An Empirical Analysis of Capital Structure and Firm#x2019;s Financial Performance in a Developing Country (Global Journal of Management and Business Research, 2019)
This paper aims to empirically study the relationship between capital structure and firm#x2019;s financial performance in a developing country like Bangladesh. The investigation has been conducted through using panel data procedure for a sample of Dhaka stock market enlisted all IT firms during the year of 2013-2017. This research works have been performed through the three performance measures including return on equity, return on asset, and earnings per share as dependent variables, where capital structure is considered as debt ratio (DR), equity ratio (ER), long-term debt ratio (LTDR), short-term debt ratio (STDR) and used as independent variables. However, descriptive statistics, correlation, pooled ordinary least square analysis, fixed effect and Random effect model has been analyzed to find the relationship between capital structure and financial performance.
Keywords: capital structure; firm performance; return on equity; return on asset; earning per share